The effect of educational intervention on self-care behavior in hypertensive older people: Applying the health belief model - Leila Naeemi; Seyedeh Shahrbanoo Daniali; Akbar Hassanzadeh; Majid Rahimi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Hypertension is a worldwide health issue. Increasing aging has given rise to the prevalence of this problem. Disease management using educational intervention based on theoretical frameworks is effective for influencing self-care behavior. The goal of this study is to investigate the effects of educational intervention on self-care behaviors that influence hypertension control among the elderly population during 2020 based on the health belief model. MATERIALS AND METHODS: A quasi-experimental study was conducted on rural older people in Ardestan, Iran. Assessments were done before and after three educational intervention sessions with a control group. The random sampling has done on 99 hypertensive elderly people in two rural centers of Ardestan from 2019 to 2020. Awareness variables, components of the health belief model, and blood pressure were assessed before and three months after the intervention. Data analysis was done using descriptive and analytical statistics. RESULTS: The study groups did not differ significantly in terms of the variables studied at the beginning of the study. After three months, the variables of awareness, self-care, and perceived sensitivity constructs, perceived severity, perceived benefits, and guide to action showed a significant rise in the experimental group compared to the control group. In addition, the effectiveness of educational intervention significantly increased self-care behavior in the experimental group. CONCLUSIONS: Educational intervention based on the health belief model can be effective to reduce the barriers of self-care behaviors. In order to have a lasting change in behavior, the use of behavioral change patterns that ecologically take into account interpersonal, organizational, and social factors is suggested too.